Bankruptcy Prediction in the Construction Sector in Lithuania - Gedminaitė, Irma (Jaunųjų mokslininkų darbai, 2017)
Due to the economic crisis and a financial market shock the number of bankruptcies has significantly increased. Bankruptcy affects businesses, shareholders, investors, creditors, employees and the public. The problem is that in most cases bankruptcy risk is identified too late. Many measures and methods for predicting bankruptcy are used but there is not one method suitable for construction companies. Thus, research was undertaken to determine which model is most appropriate infor the construction industry. Bankruptcy prediction models suggestedproposed by other authors were analysed, key financial ratios signalingsignalling bankruptcy of small and very small construction companies were identified. Analysis showed that not all models suggestedproposed by Lithuanian authors can be used inin the construction sector. The results obtained using key financial ratios, such as the net profit ratio, the quick liquidity ratio, were similar to those obtained using bankruptcy prediction models.